Screening of fungal metabolites in Brazil nuts using LC/MS/MS - Silva, Otniel Freitas (2010)
The aim of this study was to evaluate quantitatively the occurrence of fungal metabolites in Brazil nuts. Nuts were collected from Agroforest production areas in Amazon basin region. A total of 235 mycotoxins were investigated/screened by a multi-mycotoxin method based on HPLC-MS/MS. The recovery was between 56 and 136%. Fifteen mycotoxins were detected and quantified, in at least one sample; namely, aflatoxins B1, B2, G1, and M1, kojic acid, sterigmatocystin, methyl-sterigmatocystin, citrinin, cyclosporin A, cyclosporin C, cyclosporin D, cyclosporin H, rugulosin, altenariol-methylether and emodin. Aflatoxins were detected in just 1 sample (20%), but above its legal limit in Brazil and EU. Ochratoxin A and Fusarium toxins were not detected. Alternariol-methylether (from 0.75 to 3.2 g.kg-1) was detected in all five samples. This is the first study dealing with the detection of kojic acid, citrinin, cyclosporin A, cyclosporin C, cyclosporin D, cyclosporin H, rugulosin, altenariol-methylether and emodin in Brazil nuts.